2021
DOI: 10.3389/fmed.2021.639804
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Mortality Rate Among COVID-19 Patients Prescribed Statins: Data From Electronic Health Records in the US

Abstract: The severe respiratory illness due to SARS-CoV-2, the virus responsible for coronavirus disease 2019 (COVID-19), is triggered by an intense pro-inflammatory host response. Statins, prescribed primarily for lipid reduction, are known to have anti-inflammatory and immunomodulatory properties and have been associated with a reduced mortality rate among COVID-19 patients taking statins as reported in two recent retrospective studies. However, a meta-analysis that included nine studies showed that statin use did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
(52 reference statements)
2
18
0
1
Order By: Relevance
“…Our main findings show that prior statin treatment was significantly associated with a reduced risk of COVID-19 test-positivity, diagnosis, hospitalization and mortality in the 3 studied population cohorts. These findings strengthen and support evidence on the hypothesis of pleiotropic protective effects of statins in COVID-19 from prior cohort studies [23][24][25][26][27][28][29][30] and align with evidence summarized by recent meta-analyses and systematic reviews on the association of statin use and the potential protective effects against progression and severity of COVID-19 15,16,18,31,32 . A recent Swedish cohort study using register data with Table 1.…”
Section: Discussionsupporting
confidence: 86%
“…Our main findings show that prior statin treatment was significantly associated with a reduced risk of COVID-19 test-positivity, diagnosis, hospitalization and mortality in the 3 studied population cohorts. These findings strengthen and support evidence on the hypothesis of pleiotropic protective effects of statins in COVID-19 from prior cohort studies [23][24][25][26][27][28][29][30] and align with evidence summarized by recent meta-analyses and systematic reviews on the association of statin use and the potential protective effects against progression and severity of COVID-19 15,16,18,31,32 . A recent Swedish cohort study using register data with Table 1.…”
Section: Discussionsupporting
confidence: 86%
“…The beneficial role of statins in COVID-19 patients is well documented in the literature [ 10 , 29 , 54 ]. The recent implementation of statins as preventive and treatment options in COVID-19 patients has been approved by the National Health Institute in the USA [ 55 ]. Statins are considered safe, cost-effective, and beneficial in hospitalized COVID-19 patients due to their favorable clinical outcomes, as seen in our study [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have favored the use of statins in COVID-19 patients [ 10 , 29 , 54 ]. The National Health Institute in the USA has even recommended that COVID-19 patients continue statin therapy to prevent and treat cardiovascular disease [ 55 ]. This safe and cost-effective drug has been proven to be beneficial during hospitalization and linked with better clinical outcomes [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, taking into account the large number of cardio-vascular patients receiving long-term statin treatment, some recent retrospective observational clinical studies have been performed to assess a possible repercussion on the infection course. The current evidence from some separate retrospective studies in Covid-19 patients has shown that a baseline statin treatment was associated with a lower severity of disease [ [136] , [137] , [138] ] and a reduced mortality [ [139] , [140] , [141] , [142] , [143] , [144] , [145] , [146] ], although two studies did not find any association between exposure to statins and the outcome of Covid-19 infection [ 147 , 148 ]. Furthermore, some meta-analyses have been recently performed, globally revealing an overall 27–50% reduction, with respect to the control patients, in the pooled risk of developing severe form/mortality from Covid-19 [ [149] , [150] , [151] , [152] ], with the evidence of a marked patient heterogeneity in the various observations [ 151 , 152 ], in particular considering the qualitative difference between pre-admission and in-hospital use of statins [ 150 , 153 ].…”
Section: Proposed Anti-covid19 Repurposing For Statinsmentioning
confidence: 99%